Expression of recombinant human Apolipoprotein A-IMilano in Nicotiana tabacum - Wei Zhao; Lu-Yang Zhou; Jing Kong; Ze-Hao Huang; Ya-Di Gao; Zhong-Xia Zhang; Yong-Jie Zhou; Ruo-Yu Wu; Hong-Jun Xu; Sheng-Jun An (Bioresources and Bioprocessing, 2023)
Abstract Apolipoprotein A-IMilano (Apo A-IMilano) is a natural mutant of Apolipoprotein. It is currently the only protein that can clear arterial wall thrombus deposits and promptly alleviate acute myocardial ischemia. Apo A-IMilano is considered as the most promising therapeutic protein for treating atherosclerotic diseases without obvious toxic or side effects. However, the current biopharmaceutical platforms are not efficient for developing Apo A-IMilano. The objectives of this research were to express Apo A-IMilano using the genetic transformation ability of N. tabacum. The method is to clone the coding sequence of Apo A-IMilano into the plant binary expression vector pCHF3 with a Flag/His6/GFP tag. The constructed plasmid was transformed into N. tabacum by a modified agrobacterium-mediated method, and transformants were selected under antibiotic stress. PCR, RT-qPCR, western blot and co-localization analysis was used to further verify the resistant N. tabacum. The stable expression and transient expression of N. tabacum were established, and the pure product of Apo A-IMilano was obtained through protein A/G agarose. The results showed that Apo A-IMilano was expressed in N. tabacum with a yield of 0.05 mg/g leaf weight and the purity was 90.58% ± 1.65. The obtained Apo A-IMilano protein was subjected to amino acid sequencing. Compared with the theoretical sequence of Apo A-IMilano, the amino acid coverage was 86%, it is also found that Cysteine replaces Arginine at position 173, which indicates that Apo A-IMilano, a mutant of Apo A-I, is accurately expressed in N. tabacum. The purified Apo A-IMilano protein had a lipid binding activity. The established genetic modification N. tabacum will provide a cost-effective system for the production of Apo A-IMilano. Regarding the rapid propagation of N. tabacum, this system provides the possibility of large-scale production and accelerated clinical translation of Apo A-IMilano. Graphical Abstract